Teachers’ perception of social studies as a pedagogical tool for citizenship transformation and positive change in new Nigeria (2023)
Social Studies is a subject designed for knowledge, skills and values acquisition to transform citizens to become agents of change in their immediate and global environment. This study investigated teachers’ perception of Social Studies as a pedagogical tool for Citizenship transformation and positive change in new Nigeria. It was guided by three hypotheses. Descriptive survey design was adopted for the study. The population consisted of 166 Social Studies teachers from 47 public secondary schools in Ogbomoso. A total of 118 Social Studies teachers was sampled using purposive sampling technique. Teachers’ Perception of Social Studies Curriculum Questionnaire (TPSSCQ) with reliability coefficient of 0.98 was used for data collection. Percentage and Independent t- test was used to analyze the data at 0.05 level of significance. Findings from the study revealed that Social Studies curriculum content is a pedagogical tool suitable for citizenship transformation and positive change in new Nigeria. Based on these findings it was recommended that, Social Studies teachers in secondary schools should be sensitized on how to transform citizens through Social Studies contents to become agents of positive change in Nigeria.